2022
DOI: 10.3390/bios12040201
|View full text |Cite
|
Sign up to set email alerts
|

Digital Microfluidics-Powered Real-Time Monitoring of Isothermal DNA Amplification of Cancer Biomarker

Abstract: We introduce a digital microfluidics (DMF) platform specifically designed to perform a loop-mediated isothermal amplification (LAMP) of DNA and applied it to a real-time amplification to monitor a cancer biomarker, c-Myc (associated to 40% of all human tumors), using fluorescence microscopy. We demonstrate the full manipulation of the sample and reagents on the DMF platform, resulting in the successful amplification of 90 pg of the target DNA (0.5 ng/µL) in less than one hour. Furthermore, we test the efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 47 publications
(57 reference statements)
0
24
0
2
Order By: Relevance
“…Reproduced with permission from ref. 12. including cell culture, 87 polymerase chain reaction (PCR), 35,36,44,[88][89][90][91][92][93][94] isothermal amplification, 14,33,[95][96][97][98][99] and immunoassays. 100 Temperature control units are typically composed of microheaters/coolers, thermal sensors, and microcontrollers to form a close-looped control.…”
Section: Temperature Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission from ref. 12. including cell culture, 87 polymerase chain reaction (PCR), 35,36,44,[88][89][90][91][92][93][94] isothermal amplification, 14,33,[95][96][97][98][99] and immunoassays. 100 Temperature control units are typically composed of microheaters/coolers, thermal sensors, and microcontrollers to form a close-looped control.…”
Section: Temperature Controlmentioning
confidence: 99%
“…Hence, temperature control abilities are essential for DMF systems in integrated biomedical applications. So far, numerous temperature-sensitive purposes performed on EWOD platforms are present, including cell culture, 87 polymerase chain reaction (PCR), 35,36,44,88–94 isothermal amplification, 14,33,95–99 and immunoassays. 100…”
Section: System-level Integrationmentioning
confidence: 99%
“…Coelho et al [ 115 ] reported a digital microfluidics (DMF) technology made explicitly for LAMP of nucleic acid; real-time quantification was accomplished to screen the cancer biomarker c-Myc, which is linked to 45% of all human malignancies. Herein, 90 pg of the target nucleic acid (0.5 ng/L) was successfully amplified in less than an hour after completely modifying the sample and chemicals on this proposed platform.…”
Section: Nucleic Acid-based Biosensorsmentioning
confidence: 99%
“… ( A ) Schematic representation of the components, including digitally barcoded nanoparticles, microfluidic cartridge, and an integrated instrument for the detection of molecular biomarkers [ 112 ] ( B ) Working principle of the nucleic acid-based nanotweezer sensor [ 113 ] ( C ) MTase activity uncovering by padlock probe with RCA technique [ 114 ] ( D ) Multi-view of the DMF device and accumulation [ 115 ]. …”
Section: Figurementioning
confidence: 99%
“…Since their invention, microfluidics systems have attracted attention in a variety of biodiagnostic methods including PCR [ 194 ], LAMP [ 195 ], chemiluminescence-based assays [ 196 ], and immunosensors [ 24 , 197 200 ] platforms. Microfluidic immunosensors can be much more efficient and rapid than conventional immunoassay methods, due to the increase of surface-to-volume ratio that maximises mass transport in immunoreactions which, in turn, leads to a more rapid analysis [ 24 , 201 ].…”
Section: Sers-based Microfluidic Biosensorsmentioning
confidence: 99%